The Effect of Command Teaching Style and Training On the Dribbling Skills of Students of SMPN 4 Polewali - Hasyim Hasyim; Hasmyati Hasmyati; Nur Indah Atifah Anwar; Andi Atssam Mappanyukki (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to examine the effectiveness comparison of the commando teaching style with the practice teaching style on the subject matter of dribbling in the sport of football. The research method used in this study was experimental research which was conducted in 10 meetings to see the significance of the two treatments. This research was conducted at SMPN 4 Polewali with participants in this study being students who were willing to follow all research procedures. Through this sampling, the number of samples in this study amounted to 40 students. The instrument used in this study was a dribbling ability test. The results showed that the commando teaching style was better than the practice teaching style in football dribbling subjects.